Identifying the Challenges Faced by Deaf and Hard-of-Hearing Tamil Individuals in Sri Lanka: A Study on Sign Language Barriers - Sathyakumar, M.; Shivany, S.; Jegashini, K.; Dilogini, S. (University of Jaffna, 2025)
This study aims to explore the communication challenges faced by Deafness and Hard-of-Hearing (DHH) Tamil individuals in Sri Lanka, with a specific focus on sign language-related barriers and the lack of a standardised Tamil Sign Language (TSL). It investigates how these linguistic challenges affect access to education, healthcare, employment, and social integration. A qualitative approach and, phenomenological research design was employed to capture the lived experiences of Tamil-speaking DHH individuals. Data were collected through focus group discussions and community meetings using purposive and snowball sampling methods. All discussions were facilitated in Tamil Sign Language and through interpreters fluent in both Tamil and TSL. Thematic analysis was used to identify recurring challenges and experiences shared by participants. The study highlights the challenges faced by Deafness and …
Keywords: Deaf Tamil individuals;Tamil Sign Language;Communication barriers;Sri Lanka;Sign Language rights;Phenomenological study